Single use instruments for total knee arthroplasty - Michele Romeo; Giuseppe Rovere; Leonardo Stramazzo; Francesco Liuzza; Luigi Meccariello; Giulio Maccauro; Lawrence Camarda (Medicinski glasnik, 2020)
Aim: Total knee arthroplasty represents a procedure that is successfully performed to relieve functional limitation and pain in advanced stages of osteoarthritis. In the next 20 years the number of these procedures will be increased about four times. Patient specific instrumentation (PSI) has been introduced in the past years. The aim of this study was to evaluate whether SUI are more useful in clinical, organizational and economic terms. Methods: A database search about single use instrumentation (SUI) was conducted on PubMed and Google Scholar for the period 2010-2020 using the following key “total knee replacement”, “total knee arthroplasty”, “single use instruments”, and “disposable instruments”. The results of the selected studies were classified according to clinical, economic and organizational criteria. Results: The main advantage of SUI has been reported to reduce costs, timely turnover of operating rooms, maximizing the operating room utilization and patient throughput, improving the number of outpatient total joint replacements. No difference has been found other than with regard to conventional instruments in terms of clinical outcome such as hip-knee-ankle angle and other radiographic parameters, Oxford Knee Score, while a decreased infection rate has been demonstrated. Regarding the economic aspect, a reduction of direct and indirect reduction of costs has been shown for the cost of instruments reprocessing, tray sterilization, 90-day infection rate. Conclusion: The SUI can be an alternative to conventional instruments, but there are still few studies in the literature regarding clinical outcomes.
Keywords: joint replacement; prosthesis; osteoarthrosis